THE INTEGRATION OF OVERALL EQUIPMENT EFFECTIVENESS (OEE) METHOD AND LEAN MANUFACTURING CONCEPT TO IMPROVE PRODUCTION PERFORMANCE (CASE STUDY: FERTILIZER PRODUCER) - Tobe, Adi Yermia; Widhiyanuriyawan, Denny; Yuliati, Lilis (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2017)
High machine downtime and large number of rejected products is still become a big problem for company as a research object in this study. Overall Equipment Effectiveness (OEE) is one of the methods used to measure the effectiveness of a machine with three measurement factors, namely; availability rate, performance rate, and quality rate. The integration of OEE measurement and lean manufacturing analysis method is employed to improve production system in company. The measurement result shows that the value of availability rate is 88.82%, performance rate 93.70%, and quality rate 98.20%; then the OEE values obtained 81.73%. The root cause is investigated by using FMEA (Failure Mode and Effect Analysis) method particularly from the RPN (Risk Priority Number).